KEPATUHAN PAJAK GENERASI MUDA SEBAGAI CALON WAJIB PAJAK POTENSIAL (Studi pada Mahasiswa di Wilayah Jabodetabek) - Andralya Fachirainy (2021)
The higher tax revenue target results in the need for the community or taxpayers who are obedient in reporting and paying taxes in the future. As the nation's successor, the young generation is a group that has the potential to increase tax revenues so that the level of taxpayer compliance they have become needed. This study aims to determine the compliance of the young generation of taxpayers seen from the ownership of Tax Morale, paying tax awareness, and tax knowledge. The population of this study is students in Indonesia with a sample of active students who study in all universities in the areas of Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) using convenience sampling technique. The data was processed and tested using the Partial Least Square method with the application named Smart PLS 3.0. The results showed that Tax Morale, paying tax awareness, and tax knowledge had a significant positive effect on taxpayer compliance.